2016
DOI: 10.3389/fnana.2016.00027
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient In Vivo Non-viral RNA Transfection Method for Labeling the Whole Axonal Tree of Individual Adult Long-Range Projection Neurons

Abstract: We report a highly efficient, simple, and non-infective method for labeling individual long-range projection neurons (LRPNs) in a specific location with enough sparseness and intensity to allow complete and unambiguous reconstructions of their entire axonal tree. The method is based on the “in vivo” transfection of a large RNA construct that drives the massive expression of green fluorescent protein. The method combines two components: injection of a small volume of a hyperosmolar NaCl solution containing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…However, we could not determine how many types of thalamocortical projection patterns there were in the MD. Recently, a new method for axon labeling of long‐range projection neurons was reported (Porrero et al, ). The new method is based on in vivo transfection of the single‐strand palGFP–Sindbis RNA construct, and achieves more spatially precise and highly efficient single‐neuron labeling than the present method, injection of the Sindbis virus vectors.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not determine how many types of thalamocortical projection patterns there were in the MD. Recently, a new method for axon labeling of long‐range projection neurons was reported (Porrero et al, ). The new method is based on in vivo transfection of the single‐strand palGFP–Sindbis RNA construct, and achieves more spatially precise and highly efficient single‐neuron labeling than the present method, injection of the Sindbis virus vectors.…”
Section: Discussionmentioning
confidence: 99%
“…While modern technology is making the gathering of great amounts high-resolution data easier, these data would be of no use if it cannot be processed appropriately. Currently, along with simple and consistent single-cell labeling (Porrero et al, 2016) data analysis is in fact one of the two key limiting steps in connectome research (Helmstaedter, 2013): no automated projection tracing software is available that outperforms human annotators and hence most projection tracing is performed manually (but see also http://diademchallenge.org, where several algorithms can be found that were the result of an automated projection tracing-competition). Mapping all the myriad of highly diverse mouse brain neuronal networks and synapses with manual tracing may take thousands or even millions of hours.…”
Section: Criteria For Evaluating Experimental Methodsmentioning
confidence: 99%
“…In some cases, the viral vectors (e.g., retroviruses) can only infect mitotic neuronal precursors and thus can only be applied on embryonic brains. An alternative for directing the virus to a specific location is to inject or electroporate the vector RNA or DNA construct directly into the neuron in vivo (Porrero et al, 2016). …”
Section: Contemporary Neuroanatomic Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations